Differential Regulation of the Three Eukaryotic mRNA Translation Initiation Factor (eIF) 4Gs by the Proteasome - Alard, Amandine; Marboeuf, Catherine; Fabre, Bertrand; Jean, Christine; Martineau, Yvan; Lopez, Frédéric; Vende, Patrice; Poncet, Didier; Schneider, Robert J.; Bousquet, Corinne; Pyronnet, Stéphane (Frontiers in Genetics, 2019)
The 4G family of eukaryotic mRNA translation initiation factors is composed of three members (eIF4GI, eIF4GII and DAP5). Their specific roles in translation initiation are under intense investigations, but how their respective intracellular amounts are controlled remains poorly understood. Here we show that eIF4GI and eIF4GII exhibit much shorter half-lives than that of DAP5. Both eIF4GI and eIF4GII proteins, but not DAP5, contain PEST motifs in their N-termini conserved across the animal kingdom and sufficient for targeting them to the proteasome. Under normal conditions, eIF4GI and eIF4GII are protected from proteasomal destruction through binding to the detoxifying enzyme NQO1 (NAD(P)H:quinone oxidoreductase). However, when cells are exposed to oxidative stress both eIF4GI and eIF4GII, but not DAP5, are degraded by the proteasome in a PEST-dependent manner, and cell viability is more compromised upon silencing of DAP5. These findings indicate that the three eIF4G proteins are differentially regulated by the proteasome and that persistent DAP5 plays a role in cell survival upon oxidative stress.